Comprehensive analysis of serum chromogranin A and neuron‐specific enolase levels in localized and castration‐resistant prostate cancer. (14th May 2020) - Szarvas, Tibor; Csizmarik, Anita; Fazekas, Tamás; Hüttl, András; Nyirády, Péter; Hadaschik, Boris; Grünwald, Viktor; Püllen, Lukas; Jurányi, Zsolt; Kocsis, Zsuzsa; Shariat, Shahrokh F.; Sevcenco, Sabina; et al.
Abstract : Objectives: To assess chromogranin A (CGA) and neuron‐specific enolase (NSE) levels and changes in these at different stages of prostatic adenocarcinoma (PCA). Methods: Overall, 1095 serum samples from 395 patients, divided into three treatment groups, were analysed; the radical prostatectomy (RP) cohort ( n = 157) included patients with clinically localized PCA, while the docetaxel (DOC) and the abiraterone (ABI)/enzalutamide (ENZA) cohorts included 95 and 143 patients, respectively, with metastatic castration‐resistant prostate cancer. CGA, NSE and total PSA levels were measured using the KRYPTOR method. Results: Baseline CGA and NSE levels were higher in castration‐resistant (DOC and ABI/ENZA cohorts) than in hormone‐naïve, clinically localized PCA ( P < 0.001). High baseline CGA levels were independently associated with poor overall survival in both the DOC and the ABI/ENZA cohorts, with a stronger association in the ABI/ENZA cohort. In the ABI/ENZA cohort, a > 50% CGA increase at 3 months was associated with poor survival, especially in patients with high baseline CGA levels. Conclusions: The two‐ to threefold higher neuroendocrine marker levels in castration‐resistant compared to hormone‐naïve PCA support the presence of neuroendocrine transdifferentiation under androgen deprivation therapy. Our results showed patients with high baseline CGA levels who experienced a further CGA increase during ABI and ENZA treatment had the poorest prognosis. Serum CGA levels could help in tailoring and monitoring therapy in advanced PCA.